Role of Legal Practitioners in the Environmental Protection of Anambra State: A Wake up Call - Anthony Okoye (European Scientific Journal, ESJ, 2017)
The environmental challenges facing the state are numerous. In terms of the prioritization, erosion and waste management are of high priority, flooding and deforestation have medium priority while industrial pollution and biodiversity loss have low priority. State has environmental laws, but they cannot be meaningfully helpful unless their effective implementation is secured by the efforts of enforcement agencies and lawyers who deliver environmental justice. Unfortunately, lack of exposure to environmental law by members of the judiciary and most legal practitioners in the state hinders its proper implementation. The sample for this study was 121 participants drawn through convenience sampling technique. This consists of 25 legal practitioners, 25 environmentalist and 71 others from different professional areas. The instrument for data collection was a 22-item questionnaire which was made up three parts. While the legal practitioners were of the opinion that they are doing their best, the result revealed that both the environmentalists and other professionals who need the services of the legal practitioners rated their performance to be very low. Appropriate training and awareness programmes are therefore recommended so that lawyers would be better grounded to discharge this onerous duty in the state.